2019
DOI: 10.29235/1814-6023-2019-16-3-324-331
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of biomarkers of the epileptic seizures development in patients with arterial aneurysms

Abstract: The aim of the study was to establish the diagnostic significance of biochemical parameters, considered as markers of epileptic seizures in patients with arterial aneurysms (AA). 82 patients with AA (50.4 ± 11.5 year-old) with epileptic seizures (35 persons) and without them (47 persons) were examined. Before treatment, the following biochemical parameters were determined in plasma of patients: lactate, pyruvate, products reacting with thiobarbituric acid (TBA-P), antioxidant activity of the serum, activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, it has some limitations compared to PCT, such as its ability to be elevated even in non-infected and stressed states, and it is only clinically meaningful to be elevated 12 hours after the onset of inflammation, which affects its clinical specificity. 17 A study showed 18 a positive correlation between CRP levels and the degree of infection. In the present study, CRP levels in the observation group with complications were significantly higher than those in the control group without complications, which is consistent with clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has some limitations compared to PCT, such as its ability to be elevated even in non-infected and stressed states, and it is only clinically meaningful to be elevated 12 hours after the onset of inflammation, which affects its clinical specificity. 17 A study showed 18 a positive correlation between CRP levels and the degree of infection. In the present study, CRP levels in the observation group with complications were significantly higher than those in the control group without complications, which is consistent with clinical studies.…”
Section: Discussionmentioning
confidence: 99%